Genetic Diversity in Phytoplasmas from X-Disease Group Based in Analysis of idpA and imp Genes - Alessio, Florencia Ivette; Bongiorno, Vanina Aylén; Marcone, Carmine; Conci, Luis Rogelio; Fernandez, Franco Daniel (MDPI, 2025)
Phytoplasmas of the X-disease group (16SrIII) are economically significant pathogens in South America, causing severe crop losses. Traditional classification based on the 16S rRNA gene has limitations in resolving closely related strains, prompting the exploration of alternative markers. This study focuses on the immunodominant membrane proteins imp and idpA, which exhibit high variability and play crucial roles in host–pathogen interactions. Through molecular characterization of imp and idpA genes in 16SrIII subgroups, we identified significant genetic diversity and distinct evolutionary pressures. The imp gene, under positive selection, showed high variability in its hydrophilic extracellular domain, suggesting adaptation to host immune responses. In contrast, idpA exhibited strong negative selection, indicating functional conservation. Phylogenetic analyses revealed that imp and idpA provide higher resolution than the 16S rRNA gene, enabling finer differentiation within subgroups. These findings highlight the potential of imp and idpA as complementary markers for phytoplasma classification and diagnostics.